The MPC meetings, macroeconomic announcements and exchange rate behaviour in Nigeria - A. Daniel Gbadebo; A. Oluwatobi Adekunle; O. Joseph Akande; D. Wahid Olanipekun (Cogent Economics & Finance, 2021)
Literature recognise that announcement impinge shocks which could shift the mean behaviour of the exchange rate. This study apply event driven models to analyse how the expectation of daily log-exchange rate and its daily log-return respond to all the 88 MPC meetings and selected CBN's announcements that "contained information on exchange rate stabilisation" from 2 January 2005 to 25 September 2020. We establish that the log-exchange rate responds to the announcements, with and without the MPC meetings. The exchange rate is expected to depreciate in all the three days before, on the announcement day, and all the three days after the announcement. There is no sufficient evidence that either the MPC meeting or CBN announcement affects the behaviour of the log-return. Hence, unlike the MPC meetings, the announcements affects the exchange rate but not its return. We expect market participants to consider these findings in making forex decisions, and the central banks in the formulation of monetary policy.
Keywords: E58; F31; G14; 330; event driven model; exchange rate; exchange rate return; macroeconomic announcement; Monetary policy committee